1995
DOI: 10.1177/073428299501300406
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Bayley Scales of Infant Development-Second Edition and the Bayley Scales of Infant Development with Premature Infants

Abstract: The Bayley Scales of Infant Development-Second Edition (BSID-II) and Bayley Scales of Infant Development (BSID) were administered concurrently to 49 high-risk, preterm infants. Results suggested that scores from the two tests were correlated very highly. As expected, mean scores on the BSID-II were lower than on the BSID. Classification of infants as “normal,” “borderline,” and “abnormal” on each test resulted in excellent agreement for mental development scores, but only fair agreement for psychomotor scores.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…After that, the BSID- Second Edition were used. Based on a study of premature infants assessed concurrently with the BSID- First Edition and the BSID- Second Edition, we subtracted seven points from the mental developmental index (MDI) of those infants assessed with the BSID- First Edition [11]. …”
Section: Methodsmentioning
confidence: 99%
“…After that, the BSID- Second Edition were used. Based on a study of premature infants assessed concurrently with the BSID- First Edition and the BSID- Second Edition, we subtracted seven points from the mental developmental index (MDI) of those infants assessed with the BSID- First Edition [11]. …”
Section: Methodsmentioning
confidence: 99%
“…Both preterm and term infant scores on newer editions are known to be lower than those on the original version of the Bayley. 3,15,40 The use of z scores based on the mean of a control group is an effective strategy to deal with changes in developmental test norms. 41 Term comparison groups are also important to control for sociodemographic changes in preterm populations over time, such as the observed increase mean maternal age and significant decrease in number of married mothers in cohort 2.…”
Section: Figurementioning
confidence: 99%
“…Thirty-five infants (53%) were male, and fifty-six (85%) came from twoparent families. Each infant in the medically fragile group had multiple medical conditions: Forty-four percent were born prematurely (birth at less than 37 weeks gestation; Goldstein et al, 1995), and other medical conditions included central nervous system difficulties (e.g., seizure disorder), heart conditions/defects (e.g., patent ductus arteriosus), respiratory problems (e.g., bronchopulmonary dysplasia), feeding problems (e.g., swallowing disorder), organ malfunctions (e.g., hydronephrosis), skeletal disorders (e.g., osteoporosis), metabolic disorders (e.g., hyperglycemia), and infections (e.g., pneumonia). Infants were excluded from the study if they had an identified genetic disorder (other than Down syndrome), if there was known prenatal exposure to drugs or alcohol, or if their only presenting problem was parenting concerns, cerebral palsy, or developmental delay (with no Down syndrome or medical conditions).…”
Section: Subjectsmentioning
confidence: 99%
“…However, Nellis and Gridley express reservations about the application of Bayley scores for classification of young infants with developmental delays, due to the steep item gradients in the lower end of age levels, which may result in children being viewed as more or less delayed than they truly are (Nellis and Gridley, 1994). Nonetheless, in their study of concurrent administrations of the BSID and BSID-II to 49 premature infants, Goldstein et al (1995) found that, when MDI scores for BSID and BSID-II were grouped into three categories (1 standard deviation below normal, 1-2 standard deviations below normal and 2 standard deviations below normal), there was very high agreement between the two tests (kappa = 0.85) (Goldstein et al, 1995). Although the BSID-II was expected to have a major impact on the infant-toddler assessment field, no studies have examined the stability of this test with high risk infants.…”
Section: Introductionmentioning
confidence: 99%